Aktivitas Humas Wisata Setelah Pandemi: Memberdayakan Khalayak Sebagai Agen Humas Digital - Indriati Yulistiani (Lembaga Penelitian & Pengabdian Masyarakat Universitas Bina Sarana Informatika, 2022)
COVID-19 that hit the world since the end of 2019 has brought changes and impacts in people's lives. Tourism is one of the most affected industries. By looking at the situation of the community during the pandemic, which is more connected to digital media, especially social media and the main attention to health, safety and security issues, professional public relations need to formulate a new and adaptive public relations strategies and tactics. They have to modify the strategies and tactics they use before the pandemic. This paper aims to examine the most appropriate public relations strategies and tactics used to restore the glory of the tourism industry, including in Indonesia.